Numerical methods in the definition of palynological assemblage zones in the Lower Karroo (Gondwana) of Rhodesia - Falcon, Rosemary M. S. (Bernard Price Institute for Palaeontological Research, 1976)
The aim of this paper is to explore the possibility of using numerical methods in the sub-division of the palynological assemblages encountered upwards in the stratigraphic sequence in one borehole core situated in a central position in the Mid-Zambezi Basin, Rhodesia. Due to its apparently conformable thick succession and the variable micro-floras already encountered within it, this borehole has been proposed as a palynological type section for the Zambezi Basin, Rhodesia. The numerical methods used to delineate zones of similar assemblages were basically very simple, using only presence-absence data of a set range of species. The formulae employed were those of Jaccard, Simpson and Sokal (the only linear method), and the methods of classification were simplified forms of divisive or shaded half matrices, agglomerative using single linkage clustering, and spatial ordination techniques. The results support the concept of distinct changes of microfloras up the stratigraphic sequence. Groups of assemblages bearing similar microfloras appear stratigraphically adjacent to one another, barring certain minor instances of transition floras in the younger sequences. Measurable delineations or boundaries between these assemblage zones are illustrated. These numerically defined zones coincide very closely with the assemblage zones already proposed on a visual (quantitative and qualitative) basis.
Main article
Keywords: Palynology; Lower karroo; Gondwana